THE COMPARISON OF COOPERATIVE AND INDIVIDUAL LEARNING INTERACTION PATTERN IN LEARNING MODEL OF LEARNING PQ4R TO THE CONCEPTS UNDERSTANDING OF EXCRETORY SYSTEM AT SMA NEGERI 1 UBUD - Ni Wayan Septiari .; Dr. I Wayan Sukra Warpala,S.Pd,M.Sc .; Dr.I Gusti Agung Nyoman Setiawan,M.Si . (Jurnal Pendidikan Biologi undiksha, 2014)
The purpose of this research were to analys the diffrent concept understanding of excretion system between student that study using the cooperative and individual learning interaction with learning model of learning PQ4R. The study was quasi-experimental study (quasi-experimental) with the experimental design of Non-Equivalent Pre-test-post-test control group design. The study population was all students in class XI science in SMA Negeri 1 Ubud which totaled 189 students. In this study samples were taken with a simple technique Random sampling. Sample in this research is class XI science 1 and XI science 2. XI science 1 is the class that get cooperative study of interaction patterens, while XI science 2 is the class that get individual study of interaction patterens. Both of interaction patterns are used PQ4R model. The data for this research were collected by test of concept understanding student which totaled 39 question multiple choice form.The kind of data in this research is the result pos testconcept understanding of excretion system.Results of data analysis showed that there is a significant difference the concepts understandingof excretion system between students that study using the patterens of cooperative and individual learning interaction with learning model PQ4R in class XI in SMA Negeri 1 Ubud. The average value obtained by the group of students who are taughtthe patterens of cooperative learning interaction with PQ4R learning model is 77,80 and the students who are taught the patterens of individual learning interaction with PQ4R learning model is 69,44keyword : The patterens of cooperative learning interaction, The patterens of individual learning interaction, PQ4R model, concepts understanding